Effect of a Vibration System on Pain Reduction during Injection of Dental Anesthesia in Children: A Randomized Clinical Trial - Muhanad AlHareky; Jehan AlHumaid; Sumit Bedi; Maha El Tantawi; Mazin AlGahtani; Yousef AlYousef (International Journal of Dentistry)
Background. The ‘‘gate control’’ theory suggests pain can be reduced by simultaneous activation of larger diameter nerve fibers using appropriate coldness, warmth, rubbing, pressure, or vibration. This study investigated the efficacy of a device combining cold and vibration, for needle-related procedural pain in children. Methodology. A total of 51 children aged 5–12 years participated in this randomized controlled clinical trial. Half of the children were in the control group and received maxillary buccal infiltration, by injecting 1.8 ml of 2% lidocaine with 1 : 100,000 adrenaline using topical anesthesia 20% benzocaine gel for 15 seconds, while the other half were in the test group and received the same anesthesia using a commercially available external cold and a vibrating device. A face version of Visual Analogue Scale (VAS) was used as a subjective measure to assess the child’s pain experience. The parents were requested to evaluate the child’s ability to tolerate pain using a behavioral/observational pain scale. Sound, Eyes, and Motor (SEM) scale and Faces, Legs, Activity, Cry, and Consolability (FLACC) scale were used to record the child’s pain as perceived by the external evaluator. T-test or Mann–Whitney U-test was used for scale variables, paired sample T-test or Wilcoxon rank t-test was used for before and after data, and chi-square was used for categorical variable, based on the results of normality test. Results. The results showed a statistically significant reduction in pain after the injection for the test group compared with control using VAS scale (mean = 6.68 (1.09) and 8.42 (0.50); p=0.001) and FLACC scale (mean = 5.92 (1.05) and 8.16 (0.54); p=0.002), but not when using SEM scale (mean 3.22 (0.42) and 4.24 (2.74);p=0.08). Conclusions. Combined external cold and vibrating devices can be an effective alternative in reducing experienced pain and fear in children undergoing infiltration dental anesthesia. This study was registered with clinical trial registry of the United States National Institutes of Health (NIH) at ClinicalTrials.gov (NCT03953001).